STRIPPING RATIO OPTIMIZATION IN COAL MINING DESIGN USING REAL OPTION VALUATION METHOD - Pandu Tua, David
Indonesia has small amount of coal reserve compared to other countries in the world, but the demand of its coal is high, domestic and international, based on its increasing coal production since 2007. The coal reserve itself, determined by stripping ratio (SR) for the mine plan design from economic evaluation. Many mine corporations, in this case coal mine, not aware of the uncertainties especially economic uncertainty or sale price fluctuation. The corporation assume that the sale price is constant throughout the life of the mine using discounted cashflow method (DCF). Therefore, an advance method that can overcome this uncertainty is needed, that method is real option valuation (ROV). This method can determine the maximum value of SR for mine plan design based on every change in sale price. The determination can be seen from option premium value from the difference between DCF and ROV net present value. Hopefully with ROV method can increase SR value for mine design plan, so that the corporation has more coal reserve. This study can be a benchmark in determining SR value for maximum coal reserve.